2017
DOI: 10.12688/wellcomeopenres.13181.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of detecting potentially serious incidental findings during multi-modal imaging

Abstract: There are limited data on the impact of feedback of incidental Background findings (IFs) from research imaging. We evaluated the impact of UK Biobank's protocol for handling potentially serious IFs in a multi-modal imaging study of 100,000 participants (radiographer 'flagging' with radiologist confirmation of potentially serious IFs) compared with systematic radiologist review of all images.: Brain, cardiac and body magnetic resonance, and dual-energy x-ray Methods absorptiometry scans from the first 1000 imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…Brain and body imaging is increasingly used for research, diagnostic and screening purposes and is accompanied by the risk of identifying abnormalities which are unrelated to the purposes of the imaging, so-called incidental findings (IFs) [1]. Since very few IFs turn out to represent serious disease [2], it is of limited value to feedback clearly non-serious IFs. Therefore, we focus on potentially serious IFs (PSIFs), defined as those which indicate the possibility of a condition which, if confirmed, would carry a real prospect of seriously threatening life span, or of having a substantial impact on major body functions or quality of life [2].…”
Section: Introductionmentioning
confidence: 99%
“…Brain and body imaging is increasingly used for research, diagnostic and screening purposes and is accompanied by the risk of identifying abnormalities which are unrelated to the purposes of the imaging, so-called incidental findings (IFs) [1]. Since very few IFs turn out to represent serious disease [2], it is of limited value to feedback clearly non-serious IFs. Therefore, we focus on potentially serious IFs (PSIFs), defined as those which indicate the possibility of a condition which, if confirmed, would carry a real prospect of seriously threatening life span, or of having a substantial impact on major body functions or quality of life [2].…”
Section: Introductionmentioning
confidence: 99%
“…In light of these findings from the pilot and with additional advice from UKB's independent Ethics and Governance Council, we concluded that the proposed UKB imaging incidental findings protocol to use radiographer flagging (and not systematic radiologist review) provides an acceptable balance of benefit versus harm to the participants, as detailed elsewhere 12 .…”
Section: The Launch Of Uk Biobankmentioning
confidence: 87%
“…Compared to radiographer flagging, the overall balance of harms and benefits of systematic radiologist review was ultimately considered uncertain. 42 If it turns out that systematic radiologist review (or other strategies aimed at increasing the yield of incidental findings) would produce more harm than good, then we should not adopt them. However, this is not because researchers do not have a duty to look.…”
Section: Limits Of the Duty To Look For Incidental Findingsmentioning
confidence: 99%
“…Although we think that there are important unresolved questions regarding the kinds of findings that should be communicated to participants, this article takes no position on what range of incidental findings ought to be disclosed to them; we are merely arguing in favor of looking for incidental findings that should be reported to participants, whatever that range is determined to be. The German National Cohort MRI Study 20 and the U.K. Biobank Imaging Study 21 have already developed lists of potentially serious findings to report to participants. These lists were jointly developed by radiologists, clinicians, ethicists, and epidemiologists, and they are subject to ongoing review.…”
Section: Potential Strategies To Influence the Detection Of Incidentamentioning
confidence: 99%
See 1 more Smart Citation